2020
DOI: 10.1016/j.ygyno.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study comparing oncologic outcomes after lymph node assessment via a sentinel lymph node algorithm versus comprehensive pelvic and paraaortic lymphadenectomy in patients with serous and clear cell endometrial carcinoma

Abstract: h i g h l i g h t s Overall survival in non-endometrioid endometrial carcinoma appears uncompromised using a sentinel lymph node algorithm. With negative nodes, recurrence-free survival is shorter with a sentinel node algorithm, but overall survival is similar. Lymphatic recurrences do not appear increased with sentinel lymph node assessment in non-endometrioid endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 25 publications
1
49
0
4
Order By: Relevance
“…The FIRES trial, enrolling stage I patients, yielded a high sensitivity of 97% and a negative predictive value of 99.6% by SLN mapping, and prevented more people from the morbidity of LND ( 38 ). Accumulating data indicated SLN was significantly associated with accurate detection of pelvic lymph nodes and was non-inferior to LND in para-aortic nodes assessment in high risk EC patients ( 7 , 18 , 21 23 , 32 , 41 ). The pathologic ultra-staging technique adopted by SLN mapping, defines positive lymph node as macro-metastasis (≥2 mm), micro-metastasis (≥0.2 mm), and isolated tumor cells (≤0.2 mm) ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FIRES trial, enrolling stage I patients, yielded a high sensitivity of 97% and a negative predictive value of 99.6% by SLN mapping, and prevented more people from the morbidity of LND ( 38 ). Accumulating data indicated SLN was significantly associated with accurate detection of pelvic lymph nodes and was non-inferior to LND in para-aortic nodes assessment in high risk EC patients ( 7 , 18 , 21 23 , 32 , 41 ). The pathologic ultra-staging technique adopted by SLN mapping, defines positive lymph node as macro-metastasis (≥2 mm), micro-metastasis (≥0.2 mm), and isolated tumor cells (≤0.2 mm) ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experience from a study with 1,135 low risk patients indicated that 3-year OS and PFS were similar in two groups (P>0.07) ( 15 ). A multicenter study in high risk patients showed HR for association of staging approach (SLN and LND) with progression and death was 3.12 (95% CI 1.02–9.57) and 0.69 (95% CI 0.24–1.95) respectively ( 32 ). Similarly, Multinu et al ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, diagnostic accuracy of the SLN has been proven in literature both prospectively and retrospectively [ 26 , 27 , 28 , 29 , 30 , 31 ]. The current review is the first to provide a systematic overview of the available literature on lower-extremity lymphedema and post-operative complications after SLN and LND in EC, with thorough quality assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy of SLN to detect metastatic nodes in high risk EC has been reported in literature with proven high sensitivity in a multi-center, prospective cohort study [ 26 ]. Also, in a number of retrospective studies, the progression free survival was comparable in similar cohorts independent of SLN or LND [ 27 , 28 , 29 , 30 , 31 ]. Recent years have seen a steep increase in the performance of the procedure.…”
Section: Introductionmentioning
confidence: 97%
“…With the development of sentinel lymph node (SLN) mapping in EC, it has been proposed that the evaluation of retroperitoneal lymph nodes in EC is merely diagnostic and not therapeutic [20,21], though no data from randomized controlled trials are available to support this conclusion.…”
mentioning
confidence: 99%